Effects of Etomidate on Adrenal Suppression: A Review of Intubated Septic Patients. Issue 2 (February 2014) - Thompson Bastin, Melissa L.; Baker, Stephanie N.; Weant, Kyle A.
Background: Etomidate is a commonly used sedative during rapid sequence intubation (RSI). Septic patients are at an increased risk of independently developing adrenal suppression, which has been associated with increased mortality in some studies. Since etomidate affects cortisol production, its use in septic patients is controversial. However, data are still lacking to prove that etomidate should be avoided in this patient population. Objectives: The objective was to review patients diagnosed with sepsis who received etomidate during RSI. Our hypothesis is that patients who receive etomidate will experience clinically significant hypotension within the first 24 hours of intubation. Methods: A retrospective cohort study was conducted on patients intubated in the emergency department (ED) and medical/surgical floors at our institution from 2004 to 2010. Once patients with a diagnosis of sepsis were identified, it was determined whether the patients received etomidate or a different sedative during intubation. The primary endpoint was clinically significant hypotension: systolic blood pressure <90 mm Hg or mean arterial pressure <60 mm Hg. Results: One hundred fifty-seven patients, 110 etomidate and 47 non-etomidate, were included in the final analysis. Hypotension was seen in 79 (71.8%) patients who received etomidate and in 14 (29.8%) patients who received another sedative ( P ≤ .001). There were no statistically significant differences in secondary objectives. Conclusion: Etomidate use for induction of anesthesia during RSI was associated with clinically significant hypotension when compared to other sedatives. The hypotension was transient and did not translate into statistically significant differences in the secondary clinical endpoints.